Ion release and enamel remineralizing potential of miswak, propolis and chitosan nano-particles based dental varnishes. Issue 1 (April 2019) - Wassel, Mariem O.; Sherief, Dalia I.
Abstract: Purpose: Natural products can have an important role in caries control through their inherent biological abilities. Aim: The aim of the study was to compare thel remineralizing potential of alcohol and freeze-dried aqueous miswak ( Salvadora persica ) extracts (M, MFD, respectively), propolis ethanolic extract (P) and chitosan-nanoparticles (Cs-NPs) based dental varnishes either without or with 5% NaF (MF, PF, CSF-NPs) to 5% NaF varnish in primary teeth enamel samples with artificial enamel lesions. Methods: F −, Ca ++, PO4 −− ions release was assessed at 1, 2, 4 and 24 h. Surface microhardness, topography, and mineral content were assessed for primary teeth enamel before and after enamel lesion formation and after treatment and pH cycling using Knoop microhardness and SEM-EDX analysis. Results: F − was significantly released with NaF and MF, MFD varnishes; Ca ++ and PO4 −− were significantly released by Chitosan followed by miswak varnishes, while propolis varnishes released the least amount of ions. After treatment of enamel lesions and pH cycling, F − was significantly recovered by NaF, MF, and CSF-NPs descendingly, while, Ca ++, PO4 −− and surface microhardness were significantly gained by chitosan-nanoparticles and miswak varnishes. Conclusion: Chitosan-nanoparticles and miswak containing varnishes were most effective in remineralizing enamel lesions probably due to the release of F −, Ca ++, PO4 −− ions compared to NaF varnish that released F − only.